Groundwater of Volyn region: conditions of location, features of use, ways of preservation and improvement - Vovk, Oleksandr P.; Horbach, Victoriia V.; Horbach, Liudmyla M.; Nedbailo, Denys (ЛНУ імені Івана Франка, 2023)
Water is a vital resource that sustains life on our planet. However, its distribution is uneven, leading to water scarcity in some areas and excess in others. Human activities further exacerbate the reduction of usable water volume. It is predicted that water scarcity may become a significant factor in conflicts of the 21st century.Groundwater serves as a primary source of water and is classified as an exhaustible renewable natural resource. However, the replenishment of groundwater occurs at a slow rate. Given the global water scarcity issue, there is a pressing need for comprehensive research on groundwater, particularly at local and regional levels. Therefore, this article focuses on investigating the underground water resources in the Volyn region, including their occurrence, and analyzing their utilization by the local population and regional economy.The article provides a detailed description of aquifers of various geological ages in the Volyn region, including their occurrence patterns and distribution boundaries. The study examines the specific locations of each aquifer in relation to the geological structure of the area, following a geochronological sequence. Additionally, the article investigates mineralized underground waters, noting that the most prevalent types are chloride-sodium, sulfate, sodium, and hydrogen carbonate-chloride calcium waters.The study focused on the period from 2015 to 2020 to assess the current status of groundwater and identify trends in water resource utilization. The research revealed a consistent increase in the proportion of underground water in overall water usage. Surprisingly, however, the actual volume of water extracted from underground sources has been decreasing. The study examined the dynamics of water usage by various industries. It was determined that the housing and communal sector was the largest consumer of water during the study period, mainly due to the region's limited economic development and correspondingly low water demands from other sectors. Analysis showed that, on average, 25.8% and 21.3% of the total water withdrawals were utilized for industrial and agricultural purposes, respectively. Irrigation and fisheries represented the smallest water-consuming activities, accounting for 9.5% and 6.5%, respectively. Notably, a significant portion of water intake, approximately 13%, was attributed to transportation purposes.To ensure the rational utilization, preservation, and enhancement of groundwater quality, several measures have been recommended. These measures include the implementation of water-saving and water-free technologies in industrial processes, adopting reversible water usage practices, and upgrading water supply systems to improve efficiency. To safeguard and improve the quality of underground water, it is essential to upgrade treatment facilities in communal enterprises, implement rainwater and sewage treatment systems, promote the responsible use of pesticides and fertilizers in agriculture, among other practices. These actions aim to optimize water usage, mitigate pollution, and enhance the overall management of groundwater resources.The article represents a significant contribution as it provides a comprehensive description of the characteristics of underground aquifers in relation to the geological structure of the Volyn region. It establishes the distribution boundaries of underground waters of different geological ages within the region, offering valuable insights. The creation of a modern geochronological scale during the research adds further value to the study. The article also sheds light on the utilization of water resources by various economic sectors during the specified period (2015–2020), highlighting important trends. The proposed measures for preserving water resources and improving their quality demonstrate a practical approach. The research findings can serve as a valuable resource for the Department of Ecology and Natural Resources of the Volyn Regional State Administration in their efforts to develop regional environmental programs.
Keywords: underground wate; geological age; aquifer; mineral water; water intake; water supply; rational water use; conservation measures; 556.3